The Effect of Islam, Millennials, and Educated Voters to Anies-Sandi Victory of 2nd Round DKI Jakarta Governor Election In 2017 - Ruchiandrean, Riffal; Samputra, Palupi Lindiasari (UI Scholars Hub, 2020)
The aim of this article is to recognize the factors of voters that have impact to Anies-Sandi victory of 2nd round DKI Jakarta governor election in 2017. The factors that being tested are Islam voters, Millennials voters with the range of age around 21 to 40 and educated voters which voters with minimum education are senior high school in 2017. This research is quantitative research with secondary data using multiple linear regression analysis to get the empirical result. The result of this research shows that Islam, Millennials and Educated voters are simultaneously significantly impact to Anies-Sandi victory. While Islam and Millennials voters are partially significantly impact to Anies-Sandi victory but the educated voters is not significantly impact because they are considered able to think critically. Political of identity as a political marketing strategy can be used to any kind of election with the Islam, millennials, voters’ consideration but has a relatively low level of education.